A novel living ink based on Saccharomyces Cerevisae for screen printing process and its applicability in producing braille text dots. (June 2018) - Mehta, Sunita; Murugeson, Saravanan; Prakash, Balaji; Deepak,
Graphical abstract: Abstract: We examine the question whether a simple method of printing, the screen printing, can be adapted to print thin layers that grow and acquire the third dimension. Therefore, we report the formulation of a distinctive living microbes based ink suitable for screen printing process. Saccharomyces Cerevisae also known as "Baker's yeast" is used for the preparation of microbial ink and screen printability has been systematically developed by extensive rheological measurements. For this, the addition of 10%, 20% and 40% w/w triton X-100 surfactant in microbial ink is evaluated in four types of strokes (slumping, flood, mesh and squeegee) associated with screen printing and is further linked with dynamic moduli of the inks. The microbial ink with 20% w/w surfactant shows an optimized rheological properties desired for screen printing process. In order to demonstrate the applicability of the formulated ink, it has been used for screen printing braille text patterns on a normal office paper. The tactile patterns thus obtained (after growth of microbes as well as post processing treatment) are further examined for their structural retention by load bearing characterization. Another impact of this work is that it potentially enables inexpensive braille printing on common office paper, which otherwise is carried out on an expensive specialized paper.